A HISTORICAL NARRATIVE AND CRITICAL ANALYSIS OF THE ROOTS AND CAUSES OF CONFLICT IN THE SOUTHERN PHILIPPINES (Jurnal Kawistara, 2012)
This paper higlight the chronology of significant historical events, from pre-colonial times to the present, which have significantly cintributed to the conflict in Southern Philippenes. It moment, both by the Philippine government and the different Islamic liberationist group which are the main actors and players in the conflict.This paper employs both historical and structural analysis to obtain a much briader  and complete picture of the historical, socio-political, cultural, and economic realities reigning in the southern Philippines. the study shows that the problem of conflict in Mindanao is complex and complicated. thus, a much broader and careful understanding and analysis of the problem, as well as solutions that can be agreed upon by contending groups and factions toward a peaceful and negotiated approach to the mindanao peace process, are required.